Kegelâs Exercise could Reduce the Incidence of Postpartum Urinary Stress Incontinence - Arsyad, Eddy (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To investigate the cause of postpartum urinary incontinence in primigravida women and to determine the relationship between stress urinary incontinence and kegelâs exercise. Method: This was an observational study with cross sectional method, performed in institutional hospitals in Makassar. Thirty primigravida women who performed kegelâs exercise were compared with 30 primigravida women who did not perform kegelâs exercise. Data were analyzed with independent-t statistical analysis. Result: Urinary incontinence were significantly lower in primigravida women who performed kegelâs exercise (P=0.000). Conclusion: Kegelâs exercise may reduce the incidence of postpartum stress urinary incontinence. [Indones J Obstet Gynecol 2014; 2: 96-98] Keywords: kegelâs exercise, primigravida, urinary Incontinence.